Analisis Pengaruh Kualitas Website Perwalian Institut Bisnis dan Informatika Stikom Surabaya Terhadap Kepuasan Pengguna dengan Menggunakan Metode Webqual 4.0 - Milasari, Marina Tri; Nurcahyawati, Vivine; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Stikom Surabaya has several websites and one of them is a Website Perwalian. Website Perwalian is used by faculty and students to plan a schedule each semester. Website Perwalian as a media source of information about class,schedule,courses deemed to meet the information needs of students and guardian lecturers. This study was conducted to evaluate website quality of its website based on the end user satisfaction with the website’s services that is measured using Webqual 4.0 and identify important factors of performance which should be improved to meet the satisfaction of end user of Website Perwalian. Based on a sample calculation of this study and the obtained sample result is 94 respondents that will be distributed questionnaires. Multiple linear regression is used to examine the association of each dimension of Webqual 4.0 with user satisfaction. The most significant impact is on the quality of interaction for satisfaction that is equal to 28 %. This shows that the user satisfied if design Website Perwalian in accordance with the need of users. Lowest influence is on variable Usability Quality for User Satisfaction that is equal to 24.7%. It means that the web developer should pay a great attention and improvement especially in the use of navigation on Website Perwalian.Keyword: Webqual, User Satisfaction, Usability Quality, Linear Regression, Webqual